Descemet’s membrane endothelial keratoplasty for corneal endothelial failure secondary to three types of phakic intraocular lens: retrospective study - Moura-Coelho, Nuno (2023)
Purpose: To analyze the outcomes of Descemet's membrane endothelial keratoplasty (DMEK) for corneal endothelial failure secondary to phakic intraocular lens implantation (PIOL) at a reference center for corneal transplantation in Spain. Design: Retrospective, single-surgeon case series. Methods: Single-center analysis of patients who underwent DMEK for PIOL-related corneal decompensation between July 2011 and July 2020 with at least 6 months of follow-up postoperatively. The primary outcome was the final best-corrected visual acuity (BCVA, logMAR) compared to pre-DMEK BCVA. Secondary outcomes analyzed included post-DMEK refractive spherical equivalent, endothelial cell loss (%ECL), and graft failure. Results: Sixteen eyes (14 patients) underwent DMEK for PIOL-related corneal decompensation. The Mean (SD) time to PIOL explantation was 9.3 (5.0) years, and the median (P25-P75) time between PIOL explantation and DMEK surgery was 3 (2-4) months. Median pre-DMEK BCVA was 0.80 (1.08-0.60) logMAR. A statistically significant improvement in BCVA was observed 1 month after DMEK (p = 0.001), and the median final BCVA was 0.15 (0.0-0.35) logMAR (p = 0.002). The mean %ECL was 55.6 (18.7) % at 2-year follow-up and 61.7 (11.7) % in eyes with over 4 years of follow-up. Two eyes required re-bubbling (12.5%), one of which ended in primary graft failure (6.2%) and one eye had late endothelial graft failure (LEGF) at 4-year follow-up (1/15 grafts, 6.7%). Conclusion: In patients with PIOL-related corneal decompensation, DMEK leads to good and clinically significant refractive and visual outcomes in the medium-long term, with a good safety profile. Prospective studies are encouraged to ascertain whether these cases are at increased risk of accelerated endothelial cell loss and LEGF.